Tax Audit Strategy in Promoting the Improvement of Corporate Governance in the Field of Accounting - Nabila Amaro Laila Rosyda; Tjiptohadi Sawarjuwono; Daffa Putra Alvaro (Green Publisher Indonesia, 2024)
The tax audit scheme requires the WP Agency to present financial information through accounting bookkeeping. This study aims to examine DGT's strategy, one of which is tax audits in encouraging the improvement of corporate governance in accounting, considering the output of accounting, namely the company's financial statements as the basis for WP Badan to calculate the amount of tax payable in implementing the Self Assessment System (SAS) in Indonesia. This research raises prospect theory as a reference for thinking in order to interpret the behavior of WP Badan in complying with national tax policies in terms of corporate governance in the preparation and presentation of fiscal financial statements as the basis for calculating taxes deposited to the State. The methodology used is a literature study through primary and secondary data with content analysis as a data analysis technique. Research findings show that concerns that WP Badan will be subject to administrative sanctions as well as criminal sanctions due to audits will encourage WP Badan to carry out procedures in making accounting books and presenting fiscal financial statements appropriately.